A tumor-targeted trimeric 4-1BB-agonistic antibody induces potent anti-tumor immunity without systemic toxicity. Issue 1 (December 2018) - Compte, Marta; Harwood, Seandean; Muñoz, Ines; Navarro, Rocio; Zonca, Manuela; Perez-Chacon, Gema; Erce-Llamazares, Ainhoa; Merino, Nekane; Tapia-Galisteo, Antonio; Cuesta, Angel; Mikkelsen, Kasper; Caleiras, Eduardo; et al.
Abstract The costimulation of immune cells using first-generation anti-4-1BB monoclonal antibodies (mAbs) has demonstrated anti-tumor activity in human trials. Further clinical development, however, is restricted by significant off-tumor toxicities associated with FcγR interactions. Here, we have designed an Fc-free tumor-targeted 4-1BB-agonistic trimerbody, 1D8N/C EGa1, consisting of three anti-4-1BB single-chain variable fragments and three anti-EGFR single-domain antibodies positioned in an extended hexagonal conformation around the collagen XVIII homotrimerization domain. The1D8N/C EGa1 trimerbody demonstrated high-avidity binding to 4-1BB and EGFR and a potent in vitro costimulatory capacity in the presence of EGFR. The trimerbody rapidly accumulates in EGFR-positive tumors and exhibits anti-tumor activity similar to IgG-based 4-1BB-agonistic mAbs. Importantly, treatment with 1D8N/C EGa1 does not induce systemic inflammatory cytokine production or hepatotoxicity associated with IgG-based 4-1BB agonists. These results implicate FcγR interactions in the 4-1BB-agonist-associated immune abnormalities, and promote the use of the non-canonical antibody presented in this work for safe and effective costimulatory strategies in cancer immunotherapy. Cancer therapy using systemically administrated 4-1BB-targeting antibodies is often associated with severe toxicity due to the nonspecific activation of autoreactive T cells. Here, the authors have developed a trimeric antibody targeting both 4-1BB and EGFR, which activates T cells effectively and shows negligible cytotoxicity.